The Effect of Benefits and Work Discipline on Employee Productivity at The Geological Survey Center Bandung - Umulkulsum, Dara; R. Achmad Drajat Aji Suaji, (Technium Social Sciences Journal, 2020)
Performance productivity is a result of work that can be achieved by a person or group of people in an organization both quantitatively, according to their respective responsibilities and responsibilities, in an effort to achieve organizational goals, in which there is an intrinsic element that must be achieved first. in order to provide stimulation for increased performance. The intrinsic elements include the provision of allowances and work discipline. Providing allowances to employees is one of the main things that must be considered by the Bandung Geological Survey Center, because if employees do not get remuneration in accordance with the amount of sacrifice in work, then there is a potential for a decrease in discipline and an impact on performance productivity. This research is included in the category of causal associative research using a quantitative approach. Causal associative research is research that aims to determine the influence between two or more variables. This study will explain the relationship affecting and being influenced by the variables to be studied, namely the influence of allowances and work discipline variables on the productivity variables of the Bandung Geological Survey Center. The research design was carried out in a cross- sectional manner using a quantitative approach. This research was conducted at the Bandung Geological Survey Center. The results of hypothesis testing using the Structural Equation Model (SEM) with the smart PLS method found that the employee productivity variables at the Bandung Geological Survey Center were influenced by the influence of work discipline (27.34%) and the provision of allowances (9.07%) on employee productivity at the Bandung Geological Survey Center. The results of the study conclude that an expectation of productivity from performance which is influenced by discipline and provision of allowances is in accordance with the implementation of good governance as a form of bureaucratic reform that will further improve the performance of the Bandung Geological Survey Center itself.